Development of Contextual Arabic Writing (Insya’) Teaching Materials for Pesantren Students - Qudsi Mutawakil Husaini; Izzuddin Musthafa; Dindin Solahudin; Abdullah Nasir Al-Qorni (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
This study examines the challenges of teaching Arabic writing skills (insya’) in Islamic boarding schools (pesantren), where learning is often based on memorization and lacks structured, context-based teaching materials. This research aimed to develop, validate, and test the effectiveness of insya’s teaching materials to improve students’ Arabic writing skills. The study used a Research and Development (R&D) method adapted from Borg and Gall, consisting of needs analysis, design and development, expert validation, limited trial, and revision. The participants were students at Pondok Pesantren Al-Ittihad Cianjur. Data were collected through questionnaires, interviews, observations, validation sheets, and pretest–posttest writing tests. The needs analysis showed that students needed simple, step-by-step, and context-based materials related to their daily life in the pesantren. Expert validation results showed that the materials were suitable for use, with an average score of 3.71, and only minor revisions were needed. After improvements, especially the addition of varied writing exercises and better visual design, the trial showed a clear improvement in students’ writing skills. The average score increased from 65.7 to 80.6, especially in sentence structure, vocabulary, and idea organization. In conclusion, the developed insyā’ materials are valid, practical, and effective. They provide a useful model for improving Arabic instruction in pesantren through structured, context-based learning.